Neutralizing Antibody Responses to Severe Acute Respiratory Syndrome Coronavirus 2 in Coronavirus Disease 2019 Inpatients and Convalescent Patients. (4th June 2020) - Wang, Xiaoli; Guo, Xianghua; Xin, Qianqian; Pan, Yang; Hu, Yaling; Li, Jing; Chu, Yanhui; Feng, Yingmei; Wang, Quanyi
Abstract: Background: Coronavirus disease 2019 (COVID-19) is a pandemic with no specific antiviral treatments or vaccines. There is an urgent need for exploring the neutralizing antibodies from patients with different clinical characteristics. Methods: A total of 117 blood samples were collected from 70 COVID-19 inpatients and convalescent patients. Antibodies were determined with a modified cytopathogenic neutralization assay (NA) based on live severe acute respiratory syndrome coronavirus 2 and enzyme-linked immunosorbent assay (ELISA). The dynamics of neutralizing antibody levels at different time points with different clinical characteristics were analyzed. Results: The seropositivity rate reached up to 100.0% within 20 days since onset, and remained 100.0% till days 41–53. The total geometric mean titer was 1:163.7 (95% confidence interval [CI], 128.5–208.6) by NA and 1:12 441.7 (95% CI, 9754.5–15 869.2) by ELISA. The antibody level by NA and ELISA peaked on days 31–40 since onset, and then decreased slightly. In multivariate generalized estimating equation analysis, patients aged 31–45, 46–60, and 61–84 years had a higher neutralizing antibody level than those aged 16–30 years (β   = 1.0470, P  = .0125; β = 1.0613, P  = .0307; β = 1.3713, P  = .0020). Patients with a worse clinical classification had a higher neutralizing antibody titer (β = 0.4639, P  = .0227). Conclusions: The neutralizing antibodies were detected even at the early stage of disease, and a significant response was shown in convalescent patients. Abstract : The neutralizing antibody responses to severe acute respiratory syndrome coronavirus 2 in patients with COVID-19 depends on time since onset and severity of disease.